The war of the witches - Elliott, Zetta (Elliott, Zetta. Dragons in a bag (Series), 2024)
Amidst the search for a peaceful resolution, Jax and his friends find themselves facing an imminent war as the witches gear up for battle against the formidable Scourge, threatening to drain all magic from both realms.